MATERIALLY-PETROPHYSIC ESTIMATION OF THE UKRAINIAN SHIELD VOLYN MEGABLOCK GRANITOIDS FOR DETERMINATION OF THEIR PRODUCTABILITY FOR CREATION OF THE REPOSITORIES OF RADIO-ACTIVE WASTES - Kostenko, N.; Kuziv, L.; Tolstoy, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of petrophysic data by quantitative methods leading petrotypes of the Volyn megablock granitoids (Ukrainian Shield) are determined, which approach for creation in their areas of the disposals of the radioactive waste products. Interrelations between physical properties of rocks and their structural features are established.